Kajian Ontologis dan Epistimologis Tentang Aspek-Aspek Sosial Budaya dalam Masyarakat dan dalam Teks Al-Qur’an: Kajian Al-Qur’an dan Sosial Budaya - Adibah, Roichanah (Maliki Interdisciplinary Journal, 2025)
This study analyzes the socio-cultural aspects within society and the Qur’anic text through ontological and epistemological approaches. The ontological approach is applied to explain the nature and existence of socio-cultural aspects as fundamental elements in human life that contribute to building social harmony. Meanwhile, the epistemological approach is employed to explore how knowledge about socio-cultural aspects can be acquired and validated, both from the perspective of modern sciences and Qur’anic values. Through textual and contextual analysis, this research identifies several socio-cultural values embedded in the Qur'an, including justice, solidarity, compassion, and social responsibility. These values provide normative guidelines for establishing an ideal society. The epistemological examination of the Qur'an also emphasizes the importance of contextual interpretation, which considers the historical reality of its revelation, thereby producing an understanding that is relevant to contemporary socio-cultural dynamics. This study concludes that the ontological approach offers an understanding of the philosophical foundations of socio-cultural values, while the epistemological approach strengthens their validity through systematic analysis. The integration of these two approaches provides a comprehensive conceptual framework for understanding, interpreting, and applying Qur'anic socio-cultural values in the context of modern society.